Efeito da lipodistrofia na autoestima e na adesão ao tratamento antirretroviral em pessoas vivendo com HIV - Siqueira, Larissa Rodrigues (2019)
The aim of the study was to verify the effect of HIV-associated lipodystrophy on self-esteem and adherence to antiretroviral therapy (ART) in people living with HIV (PLHIV). This is a cross-sectional, comparative, descriptive and quantitative study carried out at the infectious disease outpatient clinic of the São José Hospital of Infectious Diseases in Fortaleza, Ceará. The sample was calculated to provide 80% power (β=0.20) to detect at the 5% significance level, clinically relevant differences between the strata of patients with and without lipodystrophy, in relation to the prevalence of low self-esteem. The sample was calculated in 125 participants for each stratum, totaling 250 patients. For the sampling process, a non-probabilistic convenience strategy was adopted. Inclusion criteria were: PLHIV of both sexes; aged 18 or more; on ART for 12 months or more. Exclusion requirements were: mental illness that makes it impossible to answer forms; pregnant women; homeless and deprived of their liberty in prisons. Data collection took place from June 2018 to June 2019. Data were captured by means of an interview in the private local, with an average duration of 30 minutes and application of the instruments: Sociodemographic, Clinical and Epidemiological for PLHIV; Rosenberg Self-Esteem Scale (SES); Questionnaire for Evaluation of Antiretroviral Treatment Adherence (CEAT-VIH). For statistical analysis, was used IBM SPSS Statistics version 23.0 software. Quantitative variables were analyzed by the Shapiro-Wilk test to verify the normality of the distribution. Strata of PLHIV with and without lipodystrophy were compared for clinical, sociodemographic and epidemiological characteristics. Univariate and multivariate logistic regression analysis were performed to verify the associations of self-esteem and adherence to ART with clinical, sociodemographic and epidemiological factors. The strength of the association was measured by the gross odds ratio, it´s precision (95% confidence interval) and significance (Wald test) of the estimate. In the analyzes, two-tailed test were used, considering statistically significant P<0.05. The research project was approved by the Ethics Committees of the Federal University of Ceará (No. 2.481.618) and HSJDI (No. 2.511.980), following Resolution No. 466/2012 of the National Health Council. The guidelines for observational studies were followed (Strengthening the Reporting of Observational Studies in Epidemiology - STROBE). In the total sample, 57.2% had unsatisfactory self-esteem and 57.6% adhered to ART. Self-esteem was lower in PLHIV with lipodystrophy (66.4%). In the univariate analysis, a monthly income less than or equal to two minimum wages was related to unsatisfactory self-esteem (OR: 2.94; P<0.001) and PLHIV with lipodystrophy had lower self-esteem (OR: 2.14; P=0.003). As for adherence to ART, catholics adhered better (OR: 2.50; P=0.014), and monthly income less than or equal to two minimum wages was linked to lower adherence (OR: 2.30; P=0.004). PLHIV with unsatisfactory self-esteem had more inadequate adherence to ART (OR: 3.66; P<0.001). These associations were confirmed in the multivariate analysis, in which PLHIV with monthly income less than or equal to two minimum wages (OR: 4.12; P<0.001) and those with lipodystrophy, had more unsatisfactory self-esteem (OR: 3.05; P<0.001). Catholics had better self-esteem (OR: 2.94; P=0.012), when compared to those without religion. In adherence to ART, patients with monthly income less than or equal to two minimum wages (OR: 2.15; P=0.021) and people with unsatisfactory self-esteem had inadequate adherence (OR: 2.68; P=0.001). Catholics adhered better to ART (OR: 3.13; P=0.007). In conclusion, lipodystrophy and low income negatively affect the self-esteem of PLHIV. Low income and unsatisfactory self-esteem negatively affect adherence to ART. However, religion is a protective factor for satisfactory self-esteem and adequate adherence to antiretrovirals.